The protective effect of Nigella Sativa in paracetamol induced liver toxicity in mice - MOHAMMED ABDUL MUTTALIB ABDUL BARI, (International Journal of Pharma and Bio Sciences, 2018)
Introduction Paracetamol is a safe and successful analgesic and antipyretic but it has been endorsed to more than half the cases of acute liver failure in the US and Britain. On the other hand Nigella sativa seeds, which is belonging to the botanical family of Ranunculaceae of herbaceous plants and known as black cumin seed, has been in use for centuries in Asia, Middle East, and Africa for different medical purposes. It is used as a traditional benefit for a number of ailments. In pharmaceutical field, N. sativa conjugated sterols could be used as precursors for the hemisynthesis of many hydrosoluble steroids. On the other hand Paracetamol has been correlated to more than half the cases of acute liver toxicity in the US and Britain. The aim of the Study is to investigate the possible hepatoprotective effects of N. sativa against Paracetamol induce hepatotoxicity in mice material and methodsForty adult male albino mice, included in the experiment and Paracetamol was used to induce hepatotoxicity in a dose of 1 gm /kg by the oral route. evaluation of liver damage was done by many biochemical and histopathological investigations. The result showed a potent protective effect of N. sativa against Paracetamol hepatotoxic effect as Nigella sativa in this study tended to normalize the serum levels of liver enzymes, and the protective effects has been observed clearly by the histopathological evaluation confirming that it effectively protected mouse livers against severe damage caused by Paracetamol. Conclusion in our study it shows that Nigella sativa have a very significant protective effects against paractamol induced liver toxicity which is recommended to be fully investigation on human especially to people on risk of paractamol liver toxicity.